Benson’s spiritual relaxation and lavender aromatherapy toward anxiety, sleep quality, and blood pressure - Eppy Setiyowati; Umdatus Soleha; Mulyadi Mulyadi; Muhammad Basuni (Healthcare in Low-resource Settings)
Anxiety caused by illness is one of the factors contributing to elevated hypertension across all age groups. Therefore, in addition to pharmacological treatment, non-pharmacological therapy is essential to reduce anxiety, lower blood pressure, and improve sleep quality in hypertensive patients. This study aimed to analyze the effects of Benson's spiritual relaxation and lavender aromatherapy on anxiety, sleep quality, and blood pressure in hypertensive patients. This research employed a quasi-experimental design with a pretest-posttest control group approach. The population consisted of 97 hypertensive patients at the Indonesian National Army-Navy Hospital, with a sample size of 44 respondents selected through purposive sampling. The independent variables were Benson's spiritual relaxation and lavender aromatherapy, while the dependent variables were anxiety, sleep quality, and blood pressure. Data were analyzed using multivariate analysis with a significance level of <0.05. The results indicated a significant effect of Benson's spiritual relaxation and lavender aromatherapy on anxiety (p=0.000), sleep quality (p=0.000), systolic blood pressure (p=0.000), and diastolic blood pressure (p=0.000). These techniques are simple to implement, making them a viable nursing intervention in inpatient settings and contributing to nursing science development in hospitals.